Bean inoculation associated with foliar fertilization with Cobalt and Molibdenum (Research, Society and Development, 2021)
It is believed that the use of fertilization with cobalt and molybdenum associated with inoculation with Rhizobium spp. in the bean crop is able to favor productivity, in this sense, the objective of this work was to evaluate the effect of inoculant rates and their interactions with cobalt and molybdenum in the cultivation of common beans. The experiment was carried out in the experimental field of the State University of Mato Grosso do Sul, in Aquidauana-MS. The cultivar used was Dama from the Carioca commercial group. Being carried out in a randomized block design, in a 2x5 factorial scheme, with four replications. Consisting of the presence or absence of cobalt and molybdenum foliar application and inoculant doses (0 mL, 150 mL, 300 mL, 600 mL, 1200 mL for every 50 kg of seeds). The evaluations performed were green and dry matter of nodules, green and dry matter of shoot and root, root density, number of nodules per plant, nodular activity, leaf nitrogen and phosphorus content, height of insertion of first pod, height of plants, number of branches, number of grains per pod, mass of one hundred grains and grain yield. It is concluded that the association between Rhizobium tropici and foliar fertilization, with cobalt and molybdenum in common beans, although it did not promote an increase in grain yield, resulted in improvements in the agronomic traits in the crop.